2012
DOI: 10.3892/etm.2012.843
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter thrombolytic therapy for symptomatic thrombo-occlusion of inferior vena cava filter

Abstract: Thrombus within an inferior vena cava (IVC) filter reduces filter patency and venous return from the lower extremities, and may progress to complete IVC occlusion. The clinical experiences and outcomes of transcatheter thrombolytic therapy for symptomatic IVC thrombosis following filter implantation have not been widely reported. The aim of the current study was to evaluate the efficiency and safety of trans-catheter thrombolysis for the treatment of symptomatic IVC thrombosis in patients with implanted IVC fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…A review of the literature demonstrated that little has been written about this entity. 4,[9][10][11] A recent retrospective review of 978 IVC filters placed at a major academic center found only a single case of IVC occlusion complicating filter placement. 12 Another study conducted in a referral hospital with 1718 patients who had IVC filters placed during 2001-2008 found 12 cases of total IVC occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature demonstrated that little has been written about this entity. 4,[9][10][11] A recent retrospective review of 978 IVC filters placed at a major academic center found only a single case of IVC occlusion complicating filter placement. 12 Another study conducted in a referral hospital with 1718 patients who had IVC filters placed during 2001-2008 found 12 cases of total IVC occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Because of collateral vein drainage, some patients with IVCF thrombosis may not manifest lower extremity symptoms (17). Conversely, Gurewich et al (33) reported that the resultant venous tributaries serve as alternative routes for PTE.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the present case, the predisposing condition for IVCF occlusion was presumed to be the thrombi in the patient's IVCF and APS. Xiao et al ( 17 ) reported that the development of a thrombus in an IVCF reduced filter patency and venous return from the lower extremities and that it may progress to complete IVC occlusion. Hypercoagulable/malignant conditions may affect the formation of thrombi and IVCF occlusion ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent 10-year retrospective review of patients presenting with symptomatic IVC thrombosis concluded that aggressive endovascular treatment of acute IVC thrombosis is safe and effective with an excellent short-term prognosis [ 25 ]. Combined percutaneous mechanical thrombectomy with catheter-directed thrombolysis (CDT) has been shown in several studies to optimize vascular recanalization with minimal thrombolytic dosing [ 12 , 25 - 27 ]. Although the optimal form of endovascular intervention continues to rest on expert opinion, a mechanical approach is recommended as the first-line intervention in the postoperative setting; the alternative being anticoagulation, which is supported in the literature only for nonsurgical patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%